Plates, Cells and Batteries

A skeletal layer of inert materials stabilizes the SEI film in silicon-based lithium-ion batteries, addressing volume expansion and improving cycle performance and capacity by maintaining the active material layer integrity.

JP2025504242APending Publication Date: 2025-02-06ZHUHAI COSMX BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024547622
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-03-29
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Lithium-ion batteries using silicon-based materials face volume expansion issues during charging and discharging, leading to active material layer pulverization and poor cycle performance.

Method used

Incorporating a skeletal layer rich in inert materials, such as lithium fluoride, outside the silicon-based material to stabilize the solid electrolyte interface (SEI) film, preventing volume expansion and maintaining the integrity of the active material layer.

Benefits of technology

Improves the stability of the SEI film, enhancing cycle performance and cycle life by reducing volume expansion and maintaining lithium ion utilization, thereby increasing battery capacity and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504242000001_ABST
    Figure 2025504242000001_ABST
Patent Text Reader

Abstract

The present application provides a plate, a cell and a battery. The plate according to the present application includes a current collector and an active material layer provided on at least one surface of the current collector, the active material layer includes active material particles, the active material particles include a silicon-based material, and a skeleton layer is provided outside the silicon-based material, and the proportion of fluorine element gradually increases along the direction from the silicon-based material to the skeleton layer. The plate, the cell and the battery according to the present application are used to at least solve the technical problem that the battery is prone to volume expansion.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to a Chinese patent application filed with the State Intellectual Property Office of China on June 17, 2022, bearing application number 202210688696.6 and titled "Electrode Plate and Battery", the entire contents of which are incorporated herein by reference. This application relates to the technical field of lithium ion batteries, and in particular to plates, cells and batteries. [Background technology]

[0002] Lithium-ion batteries are widely used in various fields, and with the continuous development of electronic science and technology, higher requirements are being placed on the capacity and cycle performance of batteries. In the research of lithium-ion batteries, the research and development of negative plates with good electrochemical performance has become a hot topic.

[0003] Commercialized lithium-ion batteries often use graphite-based materials as the negative electrode, but the specific capacity is only 372 mAh / g and is difficult to improve. On the other hand, silicon has a high theoretical specific capacity of 4200 mAh / g, is widely available, is inexpensive, and is environmentally friendly. Electrodes processed with silicon-based materials can significantly improve the energy density of lithium-ion batteries. However, electrodes processed using silicon-based materials expand in volume during charging and discharging, causing the active material layer to pulverize and fall off, resulting in a decrease in the cycle performance of the lithium battery.

[0004] Therefore, it is necessary to solve the problem that the electrode plates are prone to volume expansion. Summary of the Invention [Problem to be solved by the invention]

[0005] The present application provides a plate, a cell and a battery, which are used to solve at least the technical problem that the plate is prone to volume expansion. [Means for solving the problem]

[0006] In order to achieve the above object, the present application provides an electrode plate, which includes a current collector and an active material layer provided on at least one surface of the current collector, the active material layer including active material particles, the active material particles including a silicon-based material, a skeletal layer outside the silicon-based material, and a proportion of elemental fluorine gradually increasing along a direction from the silicon-based material to the skeletal layer.

[0007] The electrode plate according to the present application has a skeletal layer outside the silicon-based material, and the skeletal layer encases the silicon-based material inside, so that it can solve the problems that lithium absorption reaction occurs after the electrode plate is immersed in an electrolyte, silicon particles burst, and the SEI film repeats growth-rupture-repair and accumulates in a large amount during the growth process, causing the battery to expand, the lithium source to be consumed, the capacity to be attenuated, the initial efficiency to be low, and the cycle performance to be poor. The skeletal layer is rich in inactive materials and is favorable for improving the stability of the SEI film, so that the volume expansion of the electrode plate and the pulverization or falling off of the active material layer during the lithium absorption process can be avoided, and the effect of improving the cycle performance and cycle life can be achieved.

[0008] In one embodiment, the proportion of carbon elements increases gradually from the silicon-based material to the skeleton layer.

[0009] In one embodiment, the percentage of elemental silicon gradually decreases from the silicon-based material to the skeletal layer.

[0010] In one embodiment, elemental fluorine is present at the interface between the skeletal layer and the silicon-based material.

[0011] In one embodiment, the active material particles further include a carbon-based material distributed around the skeletal layer.

[0012] In one embodiment, elemental phosphorus is present at the interface between the skeletal layer and the carbon-based material.

[0013] In one embodiment, elemental sulfur is present at the interface between the skeletal layer and the carbon-based material.

[0014] In one embodiment, the skeletal layer comprises at least one of lithium fluoride or lithium carbonate.

[0015] In one embodiment, the silicon-based material comprises at least one of a silicon material and a silicon oxide material, and the mass of the silicon material and / or the silicon oxide material accounts for 7% to 50% of the mass of the active material particles; and / or The carbon-based material includes at least one of graphite and hard carbon.

[0016] In one embodiment, the backbone layer is an inorganic salt.

[0017] In one embodiment, the percentage of elemental carbon increases from 18% to 61% from the silicon-based material to the skeletal layer.

[0018] In one embodiment, the percentage of elemental silicon decreases from 49% to 18% from the silicon-based material to the skeleton layer.

[0019] In one embodiment, the active material layer is provided on both sides of the current collector.

[0020] The present application further provides a cell, the cell including a first plate and a second plate, the second plate being as described above.

[0021] The present application further provides a battery, the battery including a sealed case and the above-described cell located inside the sealed case. Effect of the Invention

[0022] In the electrode plate, cell and battery according to the present application, the active material layer is brought into contact with the lithium ions in the lithium material layer early during the processing of the electrode plate to form a skeletal layer, and the battery processed in this manner can reduce the loss of positive electrode lithium ions during formation, thereby improving the utilization rate of the lithium ions and the initial efficiency of the battery.

[0023] In addition to the technical problems that can be solved by the embodiments of the present application, the technical configurations constituting the technical solutions, and the technical effects of these technical configurations, other technical problems that can be solved by the plates, cells, and batteries according to the embodiments of the present application, other technical configurations included in the technical solutions, and the technical effects of these technical configurations will be described in more detail in the description of the embodiment of the present application. [Brief description of the drawings]

[0024] In order to more clearly describe the technical solutions in the embodiments of the present application or the prior art, the following briefly introduces the drawings that need to be used in the description of the embodiments or the prior art. Needless to say, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative labor. [Figure 1] FIG. 2 is a structural schematic diagram of an electrode plate according to an embodiment of the present application. [Diagram 2] FIG. 2 is a point analysis SEM image of a plate according to an embodiment of the present application. [Diagram 3] FIG. 3 is a graph showing the change in element content at positions A, B, C, and D around the silicon material in FIG. 2 of the electrode plate according to the embodiment of the present application. [Figure 4] FIG. 2 is a comparison diagram of cycle performance curves between a battery according to an embodiment of the present application and a conventional battery. [Diagram 5] FIG. 2 is a comparison diagram of cycle performance expansion curves between a battery according to an embodiment of the present application and a conventional battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] In order to make the purpose, technical solution and advantages of the present application clearer, the technical solution in the present application will be described clearly and completely below in conjunction with the drawings in the present application. Needless to say, the described embodiments are only some embodiments of the present application, but not all embodiments. Based on the embodiments in the present application, all other embodiments that a person skilled in the art can obtain without creative labor fall within the scope of protection of the present application.

[0026] Compared with graphite materials, silicon materials have the highest theoretical lithium absorption capacity of about 4200 mAh / g, which can significantly improve the capacity of batteries. However, the electrodes of silicon materials undergo serious volume expansion during the lithium absorption / release process, which makes the active material layer prone to powdering or falling off, thereby reducing the capacity and cycle life of the battery.

[0027] After the electrode plate is immersed in the electrolyte, a lithium absorption reaction occurs, and the active material layer 20 comes into contact with the lithium ions in the electrolyte to form a solid electrolyte interface (SEI film). During the charge-discharge cycle of the battery, silicon particles burst, and the SEI film repeats growth-rupture-repair and accumulates in large quantities during the growth process, causing the battery to expand, the lithium source to be consumed, the capacity to be attenuated, the initial efficiency to be low, and the cycle performance to be poor.

[0028] In view of the above background, the plate, cell and battery according to the present application have, in addition to a silicon core, an inorganic salt layer that is rich in LiF inactive material and is advantageous for improving the stability of the SEI film, thereby preventing the volume expansion of the plate and the pulverization or falling off of the active material layer during the lithium absorption process, thereby achieving the effect of improving cycle performance and cycle life.

[0029] The electrode plate, cell and battery according to the present application will be described below with reference to the drawings.

[0030] 1, the electrode plate according to the present application includes a current collector 10 and an active material layer 20 provided on at least one surface of the current collector 10. The active material layer 20 includes active material particles, the active material particles including a silicon-based material, and a skeletal layer 30 outside the silicon-based material, with the proportion of elemental fluorine gradually increasing along the direction from the silicon-based material to the skeletal layer 30.

[0031] In consideration of the problems that may occur after the electrode plate is immersed in the electrolyte, lithium absorption reaction occurs during formation, silicon particles burst, and the SEI film repeats growth-rupture-repair, causing battery expansion, lithium source consumption, capacity attenuation, low initial efficiency, and poor cycle performance, the electrode plate according to the present application has a skeleton layer 30 in addition to the silicon-based material, which is advantageous for improving the stability of the SEI film, thereby avoiding the volume expansion of the electrode plate and the pulverization or falling off of the active material layer 20 during the lithium absorption process, and achieving the effect of improving cycle performance and cycle life.

[0032] In one embodiment, the skeletal layer 30 is an inorganic salt, and the skeletal layer 30 may be formed by occluding lithium in the lithium material layer into silicon particles in the active material layer 20 .

[0033] A skeletal layer 30 may be formed outside the silicon-based material core by providing a lithium material layer on the surface of the active material layer 20. The lithium material layer is rich in metallic lithium, and generates the skeletal layer 30 by a chemical reaction between lithium and the silicon-based material.

[0034] In one embodiment, the skeletal layer 30 includes at least one of lithium fluoride (LiF) or lithium carbonate (Li2CO3). The skeletal layer 30 is rich in LiF inert material, which can effectively improve the stability of the SEI film.

[0035] The chemical reaction formula for producing the skeleton layer 30 is as follows:

[0036] PF6 - +ne - +nLi +→LiF↓+Li x PF y ↓ 2CO2+2e - +2Li + →Li2CO3↓+CO During the process of processing the electrode plate, the active material layer 20 is brought into contact with the lithium ions in the lithium material layer early, and the SEI film is formed early. A battery processed with such an electrode plate can achieve the effects of reducing the loss of positive electrode lithium ions during formation, improving the utilization rate of lithium ions, and improving the initial efficiency of the battery.

[0037] In one embodiment, the lithium material layer has an areal lithium density of 0.09 mg / cm 2 ~0.5mg / cm 2 and is provided on the surface of active material layer 20 by rolling.

[0038] In one embodiment, the presence of fluorine element at the boundary position between the skeletal layer 30 and the silicon-based material can realize the formation of an SEI film in the negative electrode plate. Since the skeletal layer 30 surrounds the silicon-based material, the boundary position between the skeletal layer 30 and the silicon-based material is the first boundary position of the skeletal layer 30. Referring to the position of point B in FIG. 2, the first boundary position of the skeletal layer 30 contacts the silicon-based material.

[0039] In one embodiment, the active material particles further include a carbon-based material distributed about the skeletal layer 30 .

[0040] In one embodiment, elemental phosphorus is present at the boundary between the skeletal layer 30 and the carbon-based material. The boundary between the skeletal layer 30 and the carbon-based material is the second boundary of the skeletal layer 30, and referring to the position of point C in FIG. 2, the second boundary of the skeletal layer 30 contacts the carbon-based material. Here, the second boundary of the skeletal layer 30 faces the first boundary of the skeletal layer 30. The elemental phosphorus has high specific capacity and rate performance, and contributes to improving the performance of the battery.

[0041] In one embodiment, elemental sulfur is included at the interface between the skeletal layer 30 and the carbon-based material, and the interface between the skeletal layer 30 and the carbon-based material is a second interface of the skeletal layer 30 .

[0042] In one embodiment, the core is a silicon-based material and the active material particles further include a carbon-based material distributed about the skeletal layer 30 .

[0043] In one embodiment, the silicon-based material includes at least one of a silicon material and a silicon oxide, and the mass of the silicon material and / or the silicon oxide material accounts for 7% to 50% of the mass of the active material particles.

[0044] In one embodiment, the carbon-based material includes at least one of graphite and hard carbon.

[0045] In one embodiment, the silicon-based material includes a silicon oxide material, the carbon-based material includes graphite, the graphite can be artificial graphite, natural graphite or modified graphite, and the mass of the silicon-based material accounts for 7% to 50% of the mass of the graphite, so that the amount of metallic lithium is compatible with the amount of the silicon-based material.

[0046] In one embodiment, the silicon-based material includes silicon particles, the carbon-based material includes a hard carbon material and graphite, and the graphite can be artificial graphite, natural graphite, or modified graphite, so that the areal density of lithium in the lithium material layer is 0.09 mg / cm 2 ~0.5mg / cm 2 This allows the amount of lithium to match the amount of silicon oxide material.

[0047] In one embodiment, the silicon based material comprises a silicon oxide material, the carbon based material comprises a hard carbon material, and the lithium material layer has an areal density of lithium of 0.09 mg / cm 2 ~0.5mg / cm 2 The mass of the silicon oxide material accounts for 7% to 50% of the mass of the hard carbon material.

[0048] In one embodiment, as shown in FIG. 1, the electrode plate according to the present application is a negative electrode plate, and the current collector 10 can be copper foil, titanium foil, nickel mesh, stainless steel foil, lithium copper alloy film or carbon cloth.

[0049] In one embodiment, the active material layer 20 may be provided on one surface of the current collector 10, or the active material layer 20 may be provided on both surfaces of the current collector 10.

[0050] In one embodiment, the lithium material layer may be an ultra-thin metallic lithium ribbon, and the ultra-thin metallic lithium ribbon is manufactured by asynchronous rolling technology. The lithium material layer is provided on the surface of the active material layer 20 by rolling so as to cover the entire surface of the active material layer 20.

[0051] In order to prevent the silicon particles from rupturing due to lithium absorption, and the SEI film from repeatedly growing, rupturing, and repairing, and accumulating in large quantities during the growth process, which leads to battery expansion, depletion of the lithium source, capacity fading, low initial efficiency, and poor cycle performance, lithium is replenished with an ultra-thin metallic lithium ribbon to construct an inorganic salt layer rich in LiF inactive material, and metallic lithium is reacted with silicon to construct an inorganic salt layer of LiF inactive material around the silicon particles.

[0052] In one embodiment, the proportion of carbon element gradually increases from the silicon-based material to the skeleton layer 30. As shown in FIG. 2 and FIG. 3, from the silicon-based material to the skeleton layer 30, that is, from the position where point A is located to the position where point D is located along the direction indicated by the arrow in FIG. 2. As shown in FIG. 3, the proportion of carbon element at the position where point A is located is 18%, the proportion of carbon element at the position where point B is located is 36%, the proportion of carbon element at the position where point C is located is 47%, and the proportion of carbon element at the position where point D is 61%. Obviously, the proportion of carbon element gradually increases from the silicon-based material to the skeleton layer 30.

[0053] In one embodiment, when the active material particles include graphite and silicon material, the proportion of elemental carbon gradually increases from the silicon-based material to the skeleton layer 30 .

[0054] In one embodiment, the percentage of silicon element gradually decreases from the silicon-based material to the skeleton layer 30. As shown in FIG. 2 and FIG. 3, from the silicon-based material to the skeleton layer 30, that is, from the position where point A is located to the position where point D is located along the direction indicated by the arrow in FIG. 2. As shown in FIG. 3, the percentage of silicon element at the position where point A is located is 49%, the percentage of silicon element at the position where point B is located is 36%, the percentage of silicon element at the position where point C is located is 28%, and the percentage of silicon element at the position where point D is located is 18%. Obviously, the percentage of silicon element gradually decreases from the silicon-based material to the skeleton layer 30.

[0055] When the active material particles contain graphite and a silicon material, the proportion of elemental silicon gradually decreases from the silicon-based material to the skeleton layer 30 .

[0056] In one embodiment, the content of phosphorus element in the silicon-based material is zero.

[0057] [Example 1] In this embodiment, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 include graphite and a silicon oxide material, and the mass of the silicon oxide material accounts for 7% of the total mass of the active material particles, so that the areal density of metallic lithium in the lithium material layer may be 0.12.

[0058] [Example 2] In this embodiment, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 include graphite and a silicon oxide material, and the mass of the silicon oxide material accounts for 20% of the total mass of the active material particles, so that the areal density of metallic lithium in the lithium material layer may be 0.22.

[0059] [Example 3] In this embodiment, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 include graphite and a silicon oxide material, and the mass of the silicon oxide material accounts for 30% of the total mass of the active material particles, so that the areal density of metallic lithium in the lithium material layer may be 0.32.

[0060] [Example 4] In this embodiment, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 include graphite and a silicon oxide material, and the mass of the silicon oxide material accounts for 40% of the total mass of the active material particles, so that the areal density of metallic lithium in the lithium material layer may be 0.42.

[0061] [Example 5] In this embodiment, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 include graphite and a silicon oxide material, the mass of the silicon oxide material accounts for 50% of the total mass of the active material particles, and accordingly, the areal density of metallic lithium in the lithium material layer may be 0.50.

[0062] In the above Examples 1 to 5, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 contain graphite and a silicon oxide material, the mass of the silicon oxide material accounts for 7% to 50% of the total mass of the active material particles, and the surface density of lithium in the lithium material layer is 0.09 mg / cm 2 ~0.5mg / cm 2 This ensures that the amount of metallic lithium contained in the lithium material layer matches the amount of silicon particles. If the amount of metallic lithium is too large, the lithium ions react with the electrolyte and precipitate, lowering the utilization rate of the lithium ions. If the amount of metallic lithium is too small, the effect of lithium replenishment is not significant, and the improvement over the initial efficiency is not significant.

[0063] [Example 6] In this embodiment, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 include a hard carbon material and a silicon oxide material, the mass of the silicon oxide material accounts for 7% of the total mass of the active material particles, and accordingly, the areal density of metallic lithium in the lithium material layer may be 0.18.

[0064] [Example 7] In this embodiment, the lithium material layer is a metallic lithium foil, the active material particles of the active material layer 20 include a hard carbon material and a silicon oxide material, and the mass of the silicon oxide material accounts for 30% of the total mass of the active material particles, so that the areal density of metallic lithium in the lithium material layer may be 0.28.

[0065] [Example 8] In this embodiment, the lithium material layer is a metallic lithium foil, the active material of the active material particles of the active material layer 20 includes a hard carbon material and a silicon oxide material, the mass of the silicon oxide material accounts for 50% of the total mass of the active material particles, and accordingly, the areal density of metallic lithium in the lithium material layer may be 0.34.

[0066] In the above Examples 6 to 8, the lithium material layer was a metallic lithium foil, the active material particles of the active material layer 20 contained a hard carbon material and a silicon oxide material, the mass of the silicon oxide material accounted for 7% to 50% of the total mass of the active material particles, and the surface density of metallic lithium in the lithium material layer was 0.09 mg / cm 2 ~0.5mg / cm 2 This allows the amount of metallic lithium to match the amount of silicon, and prevents the metallic lithium from reacting with the electrolyte and precipitating, which would otherwise cause a decrease in the utilization rate of lithium ions, due to an excessive amount of metallic lithium, while also preventing the effect of lithium replenishment or the initial efficiency from being significantly improved, due to an excessively small amount of metallic lithium.

[0067] Here, the electrode plate according to the embodiment of the present application is selected, and during processing, the active material layer 20 is coated on the surface of the current collector 10, and then baked in a dry environment at a temperature of 90°C for 24 hours, and the moisture content is controlled to 300 ppm or less to obtain a semi-finished electrode plate. Then, the lithium ingot is pressed to the micrometer level using asynchronous rolling technology to produce an ultra-thin metallic lithium ribbon, which is then combined with the semi-finished electrode plate to produce an electrode plate.

[0068] The cell according to the present application includes a first plate and a second plate as described above.

[0069] In one embodiment, the first plate is a positive plate and the second plate utilizes the plate described above as a negative plate.

[0070] The battery according to the present application includes a sealed case and a cell located inside the sealed case, the cell including a first plate and a second plate as described above.

[0071] During processing, the first electrode plate, the second electrode plate, and the separator are stacked in order, with the separator positioned between the first electrode plate and the second electrode plate to separate them. After that, the cells are wound to obtain a cell, which is then placed in a sealed case, and electrolyte is injected into the sealed case, vacuum sealed, left to stand, and chemically formed. The cells are charged at a constant current of 0.1C to a 4% state of charge (abbreviated as SOC), and then charged at a constant current of 0.2C to a 10% SOC, and then shaped and tested for capacity to obtain a pouch-type lithium-ion battery.

[0072] In one embodiment, the sealed case can be an aluminum plastic film, the electrolyte can be lithium hexafluorophosphate, and the separator is an 8 μm coated separator.

[0073] In order to demonstrate that the electrode plate according to the present application can improve the initial efficiency of the battery and improve the swelling effect of the battery through the improvement, the following tests were carried out on the produced electrode plate.

[0074] (Test 1) <Cross-section morphology test> A cross section was obtained by sputtering the electrode plate according to the present application using an ion milling (Cross section polisher, abbreviated as CP) device. It was then photographed at a magnification of 500x to 1000kx using a scanning electron microscope (abbreviated as SEM). Here, the white areas are silicon particles, and it is clear that the outside of the silicon material core is surrounded by a skeletal layer 30.

[0075] (Test 2) <Testing for the surrounding elemental content of silicon materials> The position where the image was collected by SEM was tested and analyzed by an energy dispersive spectrometer (abbreviated as EDS). Figure 2 is a point analysis SEM image of an electron microscope image at 5000 times magnification.

[0076] The direction of the arrow in FIG. 2 is the direction from the silicon-based material to the skeleton layer 30, position A is in the silicon-based material, position D is in the carbon-based material, and positions B and C are located between positions A and D. Here, position B is the boundary position between the skeleton layer 30 and the silicon-based material, and position C is the boundary position between the skeleton layer 30 and the carbon-based material, and elemental analysis for positions A, B, C and D is shown in FIG. 3. As can be seen from FIG. 3, from position A to position D, the proportion of carbon element gradually increases, the proportion of silicon element gradually decreases, and the proportion of fluorine element gradually increases to position C and then does not change further, that is, the proportion of fluorine element gradually increases to the boundary position between the skeleton layer 30 and the carbon-based material and then does not change further. In the silicon-based material, the content of phosphorus element is 0, the content of sulfur element is 0, and the content of fluorine element is 0.

[0077] As can be seen from the test results, along the direction from the silicon-based material to the skeletal layer 30, the proportion of C gradually increases and the proportion of Si gradually decreases. The element F begins to appear between position A and position C because LiF, a component of the SEI film, begins to form on the surface of the silicon particles between position A and position B. The structure of the skeletal layer 30 constructed on the surface of the silicon particles contributes to improving the stability of the SEI film, thereby avoiding the volume expansion of the electrode plate and the pulverization or detachment of the active material layer during the lithium absorption process, and achieving the effect of improving the cycle performance and cycle life of the battery. In addition, the lithium absorbed in the second electrode plate during the battery formation can be released during the cycle process, thereby improving the battery capacity.

[0078] (Test 3) <Cycle test and expansion test> Below, cycle tests and expansion tests are carried out on the batteries of two comparative examples and two experimental examples. The batteries used in the two comparative examples and the batteries used in the two experimental examples differ only in that the batteries used in the two experimental examples use the electrode plate according to the present application as the negative electrode plate, while the battery used in the comparative examples uses a conventional negative electrode plate that does not contain metallic lithium.

[0079] The test process includes the following steps: In step 1, the battery is left to stand in a temperature environment of 5°C ± 2°C for 10 minutes. In step 2, the battery is discharged to the lower limit voltage at a battery discharge rate of 0.2C and then left to stand for 10 minutes. In step 3, charge the battery at a battery charging rate of 0.7C up to the upper limit voltage, stop at 0.05C, and leave it for 10 minutes. In step 4, the battery is discharged to the lower limit voltage at a battery discharge rate of 0.2C, and then an initial capacity test is performed. In step 5, the battery is left to stand for 10 minutes. In step 6, charge the battery at a battery charge rate of 3C to the upper voltage limit, stop at 0.05C, and test the battery thickness. In step 7, the battery is left to stand in a temperature environment of 25°C ± 2°C for 10 minutes. In step 8, the battery is discharged to the lower limit voltage at a battery discharge rate of 1C and then left to stand for 10 minutes. In step 9, charge the battery at a battery charging rate of 3C up to the upper limit voltage, stop at 0.05C, and let it sit for 10 minutes. In step 9, steps 8 and 9 are repeated for 1000 cycles, in which the thickness of the battery is tested in a fully charged state every 50 cycles from 0 to 200 cycles, and the thickness of the battery is tested in a fully charged state every 100 cycles from 200 to 1000 cycles. Furthermore, steps 3 and 4 are repeated in a temperature environment of 25°C to perform a capacity test, and after completing 1000 cycles, the thickness of the battery is detected in a fully charged state.

[0080] (Test 4) <Capacity test> Using batteries with the same target capacity, four experimental examples and one comparative example were processed with different target capacities to achieve different lithium replenishment surface densities, and these batteries were placed in a constant temperature environment of 25°C, charged at a constant current and constant voltage to 4.48V at a battery charge rate of 1C, then charged at a constant voltage to stop at 0.05C, left to stand for 5 minutes, and discharged to 3V at a battery discharge rate of 0.2C, and the capacity data at 3V was compared. The results are shown in Tables 1 to 4 below.

[0081] [Table 1]

[0082] [Table 2]

[0083] [Table 3]

[0084] [Table 4]

[0085] As can be seen from Tables 1 to 4, Experimental Examples 1 to 4, which have different silicon doping amounts, different target capacities, and different lithium supplement amounts, have significantly improved 3V capacities compared to Comparative Example 1. Each battery with a different target capacity uses metallic lithium with different areal densities in the electrodes, and all of the battery capacities are improved and reach the target capacity value.

[0086] As can be intuitively seen from Tables 1 to 4, the volume expansion rate of the batteries according to the experimental examples after 100 charge / discharge cycles is lower than the volume expansion rate of the corresponding comparative battery packs after 100 charge / discharge cycles. This proves that the present application can significantly improve the technical problem that the electrodes are prone to volume expansion.

[0087] The detection result of step 9 is shown in Figure 5, where the horizontal axis represents the number of charge / discharge cycles and the vertical axis represents the expansion rate. As can be seen from Figure 5, the battery according to the present application has a lower expansion rate in a fully charged state than the conventional battery, and the improvement effect on the expansion of the battery is significant. The battery according to the present application can reduce the relative expansion during the cycle process by forming a silicate skeleton layer 30 in the second plate.

[0088] FIG. 4 is a comparison diagram of cycle performance curves of the battery according to the present application and a conventional battery, in which the horizontal axis represents the number of charge / discharge cycles and the vertical axis represents the capacity retention rate of the battery. As can be seen from FIG. 4, the capacity of the battery according to the present application decreased to 80% after completing 450 charge / discharge cycles, while the capacity of the conventional battery decreased to 80% after completing 350 charge / discharge cycles. Therefore, the battery according to the present application has improved cycle performance by about 100 charge / discharge cycles, and the capacity retention rate of the battery is improved by about 5% to 15% accordingly. This proves that the present application significantly improves the capacity and cycle performance of the battery through improvements.

[0089] It should be noted that the numerical values ​​and numerical ranges in this application are approximate values, and may have a certain range of error due to the influence of the manufacturing process, and this error can be ignored by those skilled in the art.

[0090] In addition, in the description of this application, the orientations or positional relationships indicated by terms such as "center," "length," "width," "thickness," "top end," "bottom end," "upper," "lower," "left," "right," "front," "rear," "vertical," "horizontal," "inner," "outer," "axial direction," "circumferential direction," and the like are shown based on the drawings and are merely intended to conveniently and simply explain this application. They do not indicate or imply that such positions or elements necessarily have a specific orientation or are configured and operated in a specific orientation, and therefore should not be understood as limitations on this application.

[0091] Moreover, the terms "first", "second", etc. are merely for explanatory purposes and should not be understood as indicating or implying a relative importance or implying the number of technical configurations involved. Thus, a configuration defined by "first" or "second" can explicitly or implicitly include one or more of the configurations. In the description of this application, "multiple" means at least two, e.g., two, three, etc., unless otherwise specified.

[0092] In this application, unless otherwise specified, the terms "attached", "coupled", "connected", "fixed" and the like should be understood in a broad sense. For example, they may be fixedly connected, detachably connected, or integrated, mechanically connected, electrically connected or communicatively connected to each other, directly connected, indirectly connected through an intermediate medium, or an internal communication between two elements or an interactive relationship between two elements. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific situation.

[0093] In this application, unless otherwise specified, a first configuration being "above" or "below" a second configuration may include direct contact between the first and second configurations, or may include contact between the first and second configurations through another configuration between them, rather than direct contact. Also, a first configuration being "above," "above," and "on the upper surface" of a second configuration may include the first configuration being directly above and diagonally above the second configuration, or may only indicate that the horizontal elevation of the first configuration is higher than the horizontal elevation of the second configuration. A first configuration being "below," "below," and "on the lower surface" of a second configuration may include the first configuration being directly below and diagonally below the second configuration, or may only indicate that the horizontal elevation of the first configuration is lower than the horizontal elevation of the second configuration.

[0094] Finally, the above embodiments are merely for illustrating the technical solutions of the present application, and are not limiting. Although the present application has been described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments can still be modified or part or all of the technical configurations therein can be replaced with equivalents. These modifications or replacements do not cause the essence of the corresponding technical solutions to depart from the scope of the technical solutions of the embodiments of the present application. [Explanation of symbols]

[0095] 10 Current collector 20 Active material layer 30 Skeletal Layer

Claims

1. A plate, A current collector (10) and an active material layer (20) provided on at least one surface of the current collector (10), The active material layer (20) includes active material particles, the active material particles include a silicon-based material, and a skeletal layer (30) is provided outside the silicon-based material, and the proportion of fluorine element gradually increases along the direction from the silicon-based material to the skeletal layer (30). The electrode plate characterized by the above.

2. The proportion of carbon element gradually increases from the silicon-based material to the skeleton layer (30); 2. The electrode plate according to claim 1 .

3. The proportion of silicon element gradually decreases from the silicon-based material to the skeleton layer (30); 3. The electrode plate according to claim 2.

4. A fluorine element is present at the interface between the skeletal layer (30) and the silicon-based material.

4. The electrode plate according to claim 3.

5. The active material particles further include a carbon-based material distributed around the skeletal layer (30). The electrode plate according to any one of claims 1 to 4.

6. A phosphorus element is present at the interface between the skeletal layer (30) and the carbon-based material.

6. The electrode plate according to claim 5.

7. A sulfur element is present at the boundary between the skeletal layer (30) and the carbon-based material.

7. The electrode plate according to claim 6.

8. The skeletal layer (30) contains at least one of lithium fluoride and lithium carbonate. The electrode plate according to any one of claims 1 to 4.

9. the silicon-based material comprises at least one of a silicon material and a silicon oxide material, and the mass of the silicon material and / or the silicon oxide material accounts for 7% to 50% of the mass of the active material particles; and / or The carbon-based material includes at least one of graphite and hard carbon.

6. The electrode plate according to claim 5.

10. The skeletal layer (30) is an inorganic salt. The electrode plate according to any one of claims 1 to 4.

11. The proportion of carbon element increases from 18% to 61% from the silicon-based material to the skeleton layer (30); 3. The electrode plate according to claim 2.

12. The proportion of silicon element decreases from 49% to 18% from the silicon-based material to the skeleton layer (30); 4. The electrode plate according to claim 3.

13. The active material layer (20) is provided on both sides of the current collector (10). The electrode plate according to any one of claims 1 to 4.

14. A cell, A first electrode plate and a second electrode plate according to any one of claims 1 to 13. A cell characterized by:

15. A battery, 15. A method for manufacturing a battery comprising: A battery characterized in that

Citation Information

Patent Citations

  • Silicon-based composite material as well as preparation method and application thereof

    CN113451561A

  • Metal lithium strip, negative plate and battery

    CN114335432A

  • Negative electrode for secondary battery, and secondary battery using the same

    JP2003123740A

  • Method of enhanced lithiation of doped silicon carbide via high temperature annealing in an inert atmosphere

    US8734674B1

  • Lithium-ion battery

    WO2022100626A1